Tariff Cuts, Policy Uncertainty, and the Force of Many: The Impact of Plurilateral Agreements - Lasha Chochua; Irene Iodice (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Do countries gain more by liberalizing trade together than alone? To answer this question, we study the 2015 Phase II expansion of the Information Technology Agreement (ITA), which eliminated tariffs on products covering over 12% of world trade. Market access rose by 4–6%. Nearly half of this effect reflects coordination spillovers — the extra gains from simultaneous liberalization — outweighing the roles of direct tariff cuts and reduced policy uncertainty. Exploiting quasi-experimental variation in the number of countries liberalizing each product, we show spillovers are positive once coalitions span about two-thirds of world imports — below the commonly assumed 80% critical-mass benchmark for plurilaterals. These findings show that joint liberalization yields benefits beyond the sum of individual actions — evidence of the force of many
Keywords: F13; F14; F15; F53; 330; plurilateral agreements; MFN liberalization; trade policy uncertainty; coordination spillovers; critical mass; onformation technology agreement